Clinical outcomes and adverse events in patients hospitalised with COVID‐19, treated with off‐label hydroxychloroquine and azithromycin. Issue 3 (2nd August 2020) - Kelly, Mary; O'Connor, Ròisìn; Townsend, Liam; Coghlan, Miriam; Relihan, Eileen; Moriarty, Miriam; Carr, Bernard; Melanophy, Gail; Doyle, Caitriona; Bannan, Ciaran; O'Riordan, Ruth; Merry, Concepta; et al.
Abstract : Aims: To assess clinical outcomes and adverse drug events in patients hospitalised with COVID‐19 treated with off‐label hydroxychloroquine (HCQ) and azithromycin (Az). Methods: We performed a retrospective analysis of hospitalised patients who had a positive polymerase chain reaction test for SARS‐CoV‐2 and received HCQ plus Az or no targeted therapy. The primary end point was clinical improvement on day 7 defined as either hospital discharge or an improvement of 2 points on a 6‐category ordinal scale. Secondary outcomes included mortality at day 28, intensive care admission, requirement for mechanical ventilation and incidence of adverse events. Results: Data from a total of 134 patients were evaluated; 82 patients received HCQ/Az and 52 patients received no targeted therapy. Clinical improvement was seen in 26.8% of patients who received HCQ/Az but this was not significant. The rates of intensive care transfer and mechanical ventilation were higher in the treatment group, but these differences were not significant. Mortality at day 28 was significantly higher in the treatment group ( P = .03). Hypoglycaemia elevated liver function tests and QT prolongation were monitored in both groups. The risk of QT prolongation was significantly higher in the treatment group. Treatment was stopped early in 6 (7.3%) patients due to adverse events. Conclusion: Although patients who received HCQ/Az were more severely ill the administration of these repurposed drugs did not result in clinical improvement and was associated with a significant increase in toxicity. This descriptive study highlights the importance of monitoring all repurposed agents for adverse events.